Obstetric management of the most common autoimmune diseases: A narrative review - Fernández-Buhigas, Irene (Frontiers in Global Women's Health, 2022)
Historically, women with an autoimmune disease (AD) could not get pregnant due to infertility frequently linked to the medical condition or because the pregnancy was contraindicated, as it could harm the mother and the future child. Sometimes, pregnancy was contraindicated because the medication needed to control the AD could not be given during pregnancy. All these items are no longer true nowadays. Fertility treatments have advanced, obstetric care is better, and the medical treatments of autoimmune diseases have progressed, so women with any kind of AD are encouraged to get pregnant, and their presence in obstetric clinics is arising. This is challenging for the obstetricians, as to be sure that these pregnancies are safe for the mother and the future child, the obstetricians need to know the natural evolution of these conditions, the impact of pregnancy and postpartum on the illness, and the impact of the AD in the pregnancy. In this narrative review, we aim to make a brief resume of the obstetric management of the most common diseases (Systemic lupus erythematosus, antiphospholipid syndrome, the Anti-Ro/SSA and Anti-La/SSB antigen-antibody systems, rheumatoid arthritis, Sjögren's syndrome and Undifferentiated systemic rheumatic disease and overlap syndromes).